Inhibitory Effects of Far-Infrared Ray-Emitting Belts on Primary Dysmenorrhea - Ben-Yi Liau; Ting-Kai Leung; Ming-Chiu Ou; Cheng-Kun Ho; Aiga Yang; Yung-Sheng Lin (International Journal of Photoenergy)
This study investigated the therapeutic effect of the far-infrared ray-emitting belt (FIRB) in the management of primary dysmenorrhea in female patients. Forty adolescent females with primary dysmenorrhea were enrolled in the study. Quantitative measurements were taken during the menstruation. Several parameters were measured and compared, including temperature, abdominal blood flow, heart rate variability, and pain assessment. Statistical analysis shows that treatment with FIRB had significant efficiency in increasing regional surface temperature and abdominal blood flow, widening standard deviation of normal-to-normal RR intervals, and reducing VRS and NRS pain scores. The application of an FIRB appears to alleviate dysmenorrhea.